2016
DOI: 10.1016/j.ultrasmedbio.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stone Size on the Comminution Process and Efficiency in Shock Wave Lithotripsy

Abstract: The effects of stone size on the process and comminution efficiency in shock wave lithotripsy (SWL) are investigated by experiments, numerical simulations, and scale analysis. Cylindrical BegoStone phantoms with approximately equal height and diameter of either 4-, or 7- or 10-mm, in a total aggregated mass of about 1.5 g, were treated in an electromagnetic shock wave lithotripter field. The resultant stone comminution (SC) was found to correlate closely with the average peak pressure, P+(avg), incident on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Specifically, for specimen S6 ( L / L SW = 0.18), the value of D avg is less than 10% of that in S4. This trend is consistent with the finding of Zhang et al [23] that smaller specimens require more shock doses to break, except that they tested specimens in clusters instead of individual ones. We have found that when the specimen becomes too small compared to the length of the incident shock wave, the trailing tensile phase can no longer work jointly with the leading compressive phase — through wave superpositions described in Section 3.4 — to increase damage.…”
Section: Parametric Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, for specimen S6 ( L / L SW = 0.18), the value of D avg is less than 10% of that in S4. This trend is consistent with the finding of Zhang et al [23] that smaller specimens require more shock doses to break, except that they tested specimens in clusters instead of individual ones. We have found that when the specimen becomes too small compared to the length of the incident shock wave, the trailing tensile phase can no longer work jointly with the leading compressive phase — through wave superpositions described in Section 3.4 — to increase damage.…”
Section: Parametric Studiessupporting
confidence: 92%
“…Previous studies have shown that fabricated BegoStone models can be considered as isotropic, and undergo brittle fracture under shock loading [22, 23]. Therefore, it is modeled here as a linear elastic and isotropic solid; and the constitutive equation is given by εij=1+vEσijvEσkkδij, i,j=1,2,3, where εij=12uixj+ujxi, i,j=1,2,3, is the infinitesimal strain tensor.…”
Section: Physical Model and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular in all cases considered here, a secondary fracture area appears ahead of the main fracture. The main fracture has been argued to occur at approximately 2/3 of the stone length based upon ray tracing arguments [35]. Within this interpretation the appearance of a secondary fracture area can be interpreted as arising from reflection of incoming shocks at the interface formed by the first fracture.…”
Section: Discussionmentioning
confidence: 99%
“…If uniformly distributed, the energy within the newly created fracture volume would be W fr = fW Δ V = 0.06 mJ. Focalization of P , S -waves within the stone [35] lead to increases of stress by a factor of c ≅ 3 (Fig. 8) leading to an estimate of the energy release in the fracture volume of c 2 W fr ≅ 0.5 mJ, of the same order of magnitude as Δ U tot = 0.3 mJ.…”
Section: Methodsmentioning
confidence: 99%